WARTOŚCI RODZINNE W ZWIERCIADLE UKRAIŃSKICH PAREMII - Murawska, Paulina (Studia Ukrainica Posnaniensia, 2016)
The aim of this article is the reconstruction of family values in Ukrainian proverbs and sayings. The main feature that distinguishes proverbs and sayings from other samples of oral folklore is their relevance. Therefore knowledge about the value orientation in family relationships, gained by many generations and recorded in proverbs and sayings, deserves a comprehensive study and attention.